Histological and Microbiological Effects of High-Pressure Processing (HPP) on Fresh Juice Products - Afia Saad. Alhade. Ebraheem (Journal of Scientific and Human Dimensions, 2026)
High-pressure processing (HPP) is an emerging non-thermal pasteurization technique that applies hydrostatic pressure of 100–600 MPa to food packaged in flexible, airtight containers. The goal is to extend product shelf life by inactivating unwanted microorganisms and enzymes. This paper aims to provide a detailed analysis of the effects of HPP on the histological (rheological) and microbiological properties of fresh juice products. The research reviews the scientific principles underlying the effect of high pressure on juice components, providing precise definitions of key concepts. The review documents the positive effects of HPP, which include a significant improvement in microbiological safety through a substantial reduction in bacteria, yeasts, and molds, as well as its ability to preserve sensory and nutritional properties better than conventional heat treatments. The paper also discusses the physical changes in juice viscosity resulting from high-pressure processing and their effect on texture, and how these changes relate to the activation or deactivation of enzymes such as pectin methyl esterase. The results from peer-reviewed scientific studies demonstrate that HPP technology represents a promising and effective alternative for producing high-quality, safe, and fresh juices that meet the growing consumer demand for minimally processed and healthy foods
Keywords: High-Pressure Processing; HPP; Fresh Juices; Textural Properties; Microbiological Properties; Non-Thermal Pasteurization; Shelf Life